Clinical characteristics and risk factors of Clostridioides difficile infection in children with diarrhoea - Wang, Ning; Jiang, Kun; Huang, Jinyue; Hou, Mengzhu; Wang, Lu; Wang, Wei; Fang, Yulian (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the clinical characteristics and risk factors of Clostridioides difficile infection (CDI) in children with diarrhea, and to provide evidence for the clinical prevention and treatment of CDI.MethodsThe clinical data of 192 children with diarrhoea suspected of CDI admitted from August 2020 to March 2023 were retrospectively analysed and divided into two groups according to whether CDI occurred, and the clinical characteristics and risk factors of the two groups were analysed statistically.ResultsThere were 85 cases of CDI in children with diarrhoea, 60 males (70.6%) and 25 females (29.4%), with a male to female ratio of 2.4:1; clinical manifestations were mostly fever, diarrhoea, abdominal pain, vomiting and blood in stool, with no statistically significant differences compared to the non-infected group. Interleukin - 6 (IL - 6) levels were lower in the CDI group than in the non - CDI group, and the difference was statistically significant (P < 0.05). Multi-factor logistic regression analysis was used to show that a history of hospitalisation within the last three months, a history of antibiotic treatment for ≥7 days, non-breastfeeding, and a history of antibiotic combined with probiotic treatment were risk factors for CDI in children with diarrhoea (P < 0.05).ConclusionsA history of hospitalisation within the last three months, previous antibiotic treatment for ≥7 days or combined with probiotic treatment, and non-breastfeeding are risk factors for CDI in children with diarrhoea, so children with diarrhoea who present as described above need to be alerted to CDI and are advised to have active investigations to facilitate rapid and effective control of the disease and improve prognosis.